Creation of a Low-Alcohol-Production Yeast by a Mutated SPT15 Transcription Regulator Triggers Transcriptional and Metabolic Changes During Wine Fermentation - Du, Qing; Liu, Yanlin; Song, Yuyang; Qin, Yi (Frontiers in Microbiology, 2020)
There is significant interest in the wine industry to develop methods to reduce the ethanol content of wine. Here the global transcription machinery engineering (gTME) technology was used to engineer a yeast strain with decreased ethanol yield, based on the mutation of the SPT15 gene. We created a strain of Saccharomyces cerevisiae (YS59-409), which possessed ethanol yield reduced by 34.9%; this was accompanied by the increase in CO2, biomass, and glycerol formation. Five mutation sites were identified in the mutated SPT15 gene of YS59-409. RNA-Seq and metabolome analysis of YS59-409 were conducted compared with control strain, suggesting that ribosome biogenesis, nucleotide metabolism, glycolysis flux, Crabtree effect, NAD+/NADH homeostasis and energy metabolism might be regulated by the mutagenesis of SPT15 gene. Furthermore, two genes related to energy metabolism, RGI1 and RGI2, were found to be associated with the weakened ethanol production capacity, although the precise mechanisms involved need to be further elucidated. This study highlighted the importance of applying gTME technology when attempting to reduce ethanol production by yeast, possibly reprogramming yeast’s metabolism at the global level.